Methodical Aspects of Soil Ecosystem Services Valuation (Agricultural Engineering, 2022)
Ecosystem Services Valuation is an important tool for dialogue in the decision-making process and to highlight the society’s dependence on the biosphere for well-being. Soil is the primary source of ecosystem services such as the production of food and regulating the climate, however the methodological alternatives for valuing soil ecosystem services remain poorly studied. The aim of this paper is to demonstrate methodical aspects of ecosystem services valuation, with the special attention to soil services within agricultural context. We introduce frameworks specific for soil ecosystem services. Then, we present a case study where soil ecosystem services were evaluated within agricultural context. We conclude that such valuation represents the newest trend in soil science wherein soil resources are treated in the wider context of impacts on human well-being.